The Implementation of Interactive Flipbook Learning Media in Elementary School Penggilingan 01 Jakarta - Khusnul Fatonah; Mujazi; Gunawan Wiradharma; Muhammad Rijal Fadli (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
One of the problems experienced by teachers at Penggilingan 01 Elementary School, Jakarta, is the need for teacher skills in using digital-based learning media. Teachers use PowerPoint media and several online quizzes on the website for classroom learning. However, more is needed because students need more varied learning media to strengthen their enthusiasm for learning. On that basis, the community service team from Esa Unggul University implemented a community service program entitled The Implementation of Interactive Flipbook Learning Media in Penggilingan 01 Elementary School, Jakarta. The objectives of this activity are 1) to provide an understanding to teachers at the school about the benefits and how to make interactive flipbook learning media, 2) to develop teacher skills in optimizing various features in interactive flipbooks, and 3) to encourage active student participation in the learning process through interactive flipbook media. The method of this activity is carried out in five stages, namely socialization, training, application of technology, mentoring and evaluation, and program sustainability. The results obtained from this activity show that teachers at Penggilingan 01 Elementary School, Jakarta, have skills in making digital-based learning media. This is proven in the form of products, or teacher works in the form of interactive flipbook learning media. In addition, teachers have good management skills in designing learning materials, designing content, optimizing various interactive flipbook features, and implementing them in classroom learning.